Watak Manusia Dalam Naskah Geguritan Joharsa - Mukhtaruddin Mukhtaruddin (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
The study of Balinese manuscripts Classical Islamic religious nuanceis done using philological approach and method of content analysis basedon the framework of semio tic analysis of Roland Barthes post-structural.Stages of this research include the transfer of language or transliterationof the manuscript into Indonesian. After that, then the manuscript wastranslated into Indonesian. Indonesian-language translation is beinganalyzed. Geguritan Joharsa analyzed in this report only 4 Canto, namelyCanto 19 to Canto 22. Geguritan Joharsa Canto 19 to Canto 22 describes thecharacter of each actor in this geguritan. Those cantos describe good humannature and human nature is not good.Human nature is well refected by Joharsa, Narawulan and Nahodaas perpetrators. Joharsa has noble character exemplary human beings.Character is very important in family life and in public life. Character inaccordance with Joharsa is Narawulan. She has devoted to her husband’scharacter. She faced a diffcult life very hard, but she remained faithful to herhusband until met. Nahoda character is like to distance them from the worldand like to help with no strings attached. Which is not good character playedby King Lokantara. King has a character Lokantara arrogant and angry.Key Words: Geguritan Joharsa, Human Character